Reconfiguring Hanafi Jurisprudence in Central Asia: A Comparative Study of Contemporary Uzbek Islamic Legal Thought and Classical Transoxanian Usul al-Fiqh - Ghazal Lianne; Jouri Tuleen; Izza Afkarina Rahman; Nursultan Daulet; Shamil Alyautdinov (Indonesian Journal of Islamic Law, 2025)
This article explores the evolution of Hanafi legal theory in Central Asia, with a comparative analysis of contemporary Uzbek Islamic legal thought and the classical Transoxanian Usul al-Fiqh tradition. The study investigates how historical developments and socio-political transformations have influenced the interpretation and application of Hanafi principles in modern Uzbekistan. Drawing from textual analysis of classical Usul al-Fiqh manuscripts, contemporary legal documents, and interviews with Islamic scholars in Uzbekistan, this research situates modern Uzbek Islamic jurisprudence within its historical and regional context. The findings highlight key continuities and divergences in the methodologies employed by contemporary Uzbek jurists compared to their classical Transoxanian predecessors. These include shifts in prioritizing textual over rationalist interpretations, the role of state authority in shaping legal discourse, and the increasing incorporation of public policy considerations within Islamic legal reasoning. The study also examines how these changes reflect broader trends in Islamic legal reform across post-Soviet Central Asia. This article concludes that while contemporary Uzbek Islamic legal thought retains a foundational connection to classical Hanafi principles, it represents a localized adaptation influenced by modern challenges, including legal pluralism and state interventions. The analysis underscores the importance of understanding historical and cultural contexts in shaping Islamic legal traditions. It contributes to broader discussions on the dynamic interplay between classical jurisprudence and modernity in Muslim societies.